2013
DOI: 10.1039/c3sc51211h
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazoles as versatile directing group for selective sp2 and sp3 C–H activation: cyclization vs substitution

Abstract: Selective cyclization and substitution was achieved with designated 1,2,3-triazole acid auxiliary groups under Pd catalyzed C-H activation conditions. Both sp 2 and sp 3 C-H bonds were effectively activated,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
83
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(87 citation statements)
references
References 66 publications
1
83
0
3
Order By: Relevance
“…[10] In contrast, the development of analogous routes to saturated N heterocycles on the basis of C(sp 3 )ÀH amination has remained a challenge. [11][12][13] Recently, the research groups of Daugulis and Chen independently developed elegant methods for the palladium-catalyzed intramolecular amination of primary C(sp 3 ) À H bonds to form azetidines, pyrrolidines, and indolines. [12] Subsequently, Shi and co-workers reported an example of the intramolecular amination of primary C(sp 3 )ÀH bonds with a triazole acid auxiliary as a directing group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] In contrast, the development of analogous routes to saturated N heterocycles on the basis of C(sp 3 )ÀH amination has remained a challenge. [11][12][13] Recently, the research groups of Daugulis and Chen independently developed elegant methods for the palladium-catalyzed intramolecular amination of primary C(sp 3 ) À H bonds to form azetidines, pyrrolidines, and indolines. [12] Subsequently, Shi and co-workers reported an example of the intramolecular amination of primary C(sp 3 )ÀH bonds with a triazole acid auxiliary as a directing group.…”
mentioning
confidence: 99%
“…[12] Subsequently, Shi and co-workers reported an example of the intramolecular amination of primary C(sp 3 )ÀH bonds with a triazole acid auxiliary as a directing group. [13] We envisioned that methodology for the synthesis of N heterocycles through the amination of secondary C(sp 3 ) À H bonds would be a valuable addition to the heterocyclic chemistry toolkit and offer a new retrosynthetic disconnection for access to commonly encountered structural motifs. [15] We envisioned that our new PIP directing group would meet these challenges through careful tuning of the reaction conditions.…”
mentioning
confidence: 99%
“…[3][4][5] The group of Yu showed that N-triflated phenethylamines could be converted into indolines using a range of oxidants with palladium as a catalyst.…”
mentioning
confidence: 99%
“…[5] The synthesis of azetidine, indoline, and carbazole derivatives through directed C À H functionalization, via five-or six-membered palladacycles, is well developed. [6] However, there have been few reports of directed C À H functionalizations, via seven-membered palladacycles, to synthesize sixmembered heterocycles, [7] because the formation of a sevenmembered palladacycle intermediate during the catalytic cycle is more difficult than that of five-or six-membered palladacycles.…”
mentioning
confidence: 99%
“…[8] Recently, Ye reported the application of 1,2,3-triazole-4-carboxylic acid derivatives as alternative auxiliaries in adjusting the palladium-catalyzed C À H activation. [9] In 2008, Ackermann reported carboxylic acids as cocatalysts for generally applicable direct arylations in apolar solvents. [10] In 2009, Ackermann also reported the ruthenium-catalyzed direct arylations of N-aryl-1,2,3-triazoles with aryl chlorides as electrophiles.…”
mentioning
confidence: 99%